A Comparison of the Effects of Midazolam/Fentanyl and Midazolam/Tramadol for Conscious Intravenous Sedation During Third Molar Extraction - GARİP, HASAN; GÖNÜL, ONUR (W B SAUNDERS CO-ELSEVIER INC, 2011)
Purpose: This study evaluated the effects of fentanyl and tramadol, used in combination, as sedation for third molar surgical extraction. Patients and Methods: This prospective, randomized, double-blind, placebo-controlled study included 60 patients undergoing extraction of a horizontal third molar with an Amsterdam Preoperative Anxiety and Information Scale score above 10 points. All of the patients were first given a 0.03-mg/kg bolus of midazolam, and then they were randomized into 3 groups: group A, midazolam only; group B, midazolam and 1-mu g/kg fentanyl; and group C, midazolam and 1-mg/kg tramadol. The vital signs were recorded. Patients were assessed for postoperative pain and adverse effects, and patient and surgeon satisfaction was assessed. Results: No differences were found in the heart rate among groups (P > .05). The mean blood pressure was also similar until the 40th minute, after which the mean blood pressure in the patients in group A was lower than that in the other 2 groups (P < .01). In the postoperative pain assessment, the visual analog scale scores of the patients in group C were lower than those in the other 2 groups in the first postoperative hour (P < .05). The time at which the first rescue analgesic was taken in groups A, B, and C was 3, 3.5, and 5 hours postoperatively, respectively, and was significantly later in group C (P < .01). No difference was found in patient/surgeon satisfaction among the groups. Conclusions: Tramadol has a better analgesic effect in third molar surgery than fentanyl and placebo. (C) 2011 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 69:1594-1599, 2011
Keywords: PATIENT-CONTROLLED SEDATION; PREVENTING POSTOPERATIVE PAIN; ANALGESIC EFFICACY; TRAMADOL; REMIFENTANIL; COMBINATION; 3RD-MOLAR; RECOVERY; FENTANYL; PLACEBO